Aspek-Aspek Psikologis pada Prosesi Rambu Solo’ (Tinjauan Teori Religiusitas) - Lusi, Reyvences Asgrenil; Yuwanto, Listyo (Universitas Muhammadiyah Jember, 2020)
This literature review aims to review the psychological aspects, especially the religiosity aspects contained in the implementation of the Rambu Solo’ procession in the Toraja tribes. Rambu Solo’ is the procession of delivering or burying the dead by their families to the spiritual realm or puya (heaven). In its implementation, there are adjustments as well as shifts in the implementation of the Rambu Solo’ procession